Experimental Study of The Potential for Energy Absorption and Drying Time of Coffee Beans Using a Dome Dryer Type Dryer in The Sukmailang Area of Pesawaran Regency - Santoso, Yopi Rusdian; Afisna, Lathifa Putri; Syaukani, Muhammad; Saragih, Gita Johannes (UIR PRESS, 2023)
The traditional drying method has many weaknesses, namely it is very dependent on the weather, so that drying takes a long time. Traditional drying methods result in frequent contamination of dust, dirt, insects, and if wet they are prone to moss growth due to delays in drying during cloudy or rainy weather. This study designed a coffee bean dryer with electric power which is the result of converting solar energy with the help of photovoltaic which is first stored in the battery. The main components of this tool are: drying chamber, drying roof, tray, thermostat, heating element, this test is carried out to determine changes in seed moisture content, required power and efficiency. The temperature is set at 50°C with a fan speed of 3m/s. The fastest decrease in water content occurred in the mass of 1 kg coffee bean samples starting on June 22, 2022 from 28.5% water content to 12% moisture content. Meanwhile, the longest decrease in the water content of coffee beans was at a mass of 2 kg coffee beans on June 24, 2022, the initial water content of coffee beans was 29.3% to 13.2%. The greater the mass of the coffee beans to be dried, the greater the time required to dry the coffee beans using a dome dryer. The maximum power is in the Sukmailang area, Pesawaran district which has a plateau as high as 1200 meters above sea level (MDPL) with an average power of 11.38 Watt. The highest power is produced at 12:00 WIB with a value of 16.49 Watts. The use of solar panels in the Sukmailang area, Pesawaran Regency which has a plateau as high as 1200 (MDPL) is still not effectively utilized because the results obtained have an average efficiency value of 2.22%